Exposição aos microplásticos em ambientes internos: revisão sobre as fontes e impactos à saúde humana - Souza, Luís Gustavo Diniz de (Universidade Federal de São Carlos, 2025)
The continuous degradation of plastic waste, driven by physical and chemical processes, has resulted in the dispersion of microplastics (MPs) across diverse environmental compartments. However, scientific literature has prioritized outdoor environments, while indoor environments where MP concentrations frequently exceed those found outdoors do not receive the same attention. This work conducts a literature review on MP exposure in indoor environments, analyzing their sources, characteristics, and potential health risks. The review identifies that indoor spaces are accumulation zones, dominated by fibers of textile origin, such as polyethylene terephthalate (PET) and polypropylene (PP), and that exposure occurs primarily through inhalation and dust ingestion. Toxicological evidence points to risks such as oxidative stress and inflammation, with the finding that MPs can translocate into the bloodstream and have already been detected in tissues such as the lungs, liver, and human placentas. Therefore, indoor air quality is established as a relevant public health issue, and mitigation requires a coordinated approach.
Exposure to microplastics in indoor environments: a review of sources and impacts on human health
Keywords: Microplástico ambientes internos; Exposição humana; Fibras; Toxicidade; Microplastics; Indoor environments; Human exposure; Fibers; Toxicity; CIENCIAS EXATAS E DA TERRA::QUIMICA; 3. Saúde e Bem-Estar